2005
DOI: 10.1080/13576500442000049
|View full text |Cite
|
Sign up to set email alerts
|

Laterality of hand function in naturalistically housed chimpanzees (Pan troglodytes)

Abstract: Studies of laterality of hand function in chimpanzees (Pan troglodytes) have the potential to tell us about the origins of handedness in Homo sapiens. However, the data are confusing, with discrepancies present between studies done in the field and the laboratory: the former show wild chimpanzees to be unlateralised at the population level, while the latter show captive chimpanzees as lateralised at the population level. This study of 26 semi-free ranging chimpanzees of Chester Zoo, UK, aimed to investigate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
5
36
2
Order By: Relevance
“…The distinction between species level and population level preferences is important. Each approach, although equally valid, addresses different questions: species level shows that handedness is fixed genetically, whereas population level indicates that there is flexibility in the genetic control of handedness, where environmental factors might have greater influence on the expression of handedness [Fletcher and Weghorst, 2005]. If the evolution of human handedness is the main aim of investigation, then finding a species level preference must be the goal.…”
Section: Limb Preference In Bonobosmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction between species level and population level preferences is important. Each approach, although equally valid, addresses different questions: species level shows that handedness is fixed genetically, whereas population level indicates that there is flexibility in the genetic control of handedness, where environmental factors might have greater influence on the expression of handedness [Fletcher and Weghorst, 2005]. If the evolution of human handedness is the main aim of investigation, then finding a species level preference must be the goal.…”
Section: Limb Preference In Bonobosmentioning
confidence: 99%
“…However, other studies, particularly of wild populations, have not found significant hand preference [Heestand, 1986;Hopkins, 1993;Hopkins et al, 1993a;Marchant and McGrew, 1996;McGrew and Marchant, 2001;Marchant and McGrew, 2007]. A comprehensive study of naturalistically housed chimpanzees replicating the methods used in studies in the wild [Marchant and McGrew, 1996;McGrew and Marchant, 2001] found that the population as a whole was largely unlateralised [Fletcher and Weghorst, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Rearing chimpanzees by righthanded humans presumably causes captive-born chimpanzees to be more right-handed than wild-born individuals. As a means of testing this hypothesis, the HI scores from the combined wild chimpanzee data were compared with the HI scores provided in three previously published reports of hand use for tool-use tasks in captive chimpanzees (n ϭ 29) that mimic the demands of termite-fishing in wild chimpanzees (49)(50)(51)(52). In the captive studies, the chimpanzees needed to probe with sticks to extract food (yogurt or honey) from an artificial termite mound.…”
Section: Comparison With Previous Studies On Hand Use For Termite Fismentioning
confidence: 99%
“…For example, in the two studies of handedness in wild chimpanzees with the largest sample sizes McGrew & Marchant, 2001), hand use for daily actions was measured. Hand use in each study was based on the 10 or 15 most frequent behaviors, all of which were behaviors that did not induce significant preferences at the individual level (see also Fletcher & Weghorst, 2005). These behaviors included scratch, groom, eat, pluck, pull, nose wipe, pincer, pick up, hold, and cradle.…”
Section: Potential Explanations For Discrepancies Between Studies Andmentioning
confidence: 99%